Electric field manipulation enhanced by strong spin-orbit coupling: promoting rare-earth ions as qubits. Issue 10 (27th June 2020) - Liu, Zheng; Wang, Ye-Xin; Fang, Yu-Hui; Qin, Si-Xue; Wang, Zhe-Ming; Jiang, Shang-Da; Gao, Song
Abstract: Quantum information processing based on magnetic ions has potential for applications as the ions can be modified in their electronic properties and assembled by a variety of chemical methods. For these systems to achieve individual spin addressability and high energy efficiency, we exploited the electric field as a tool to manipulate the quantum behaviours of the rare-earth ion which has strong spin-orbit coupling. A Ce:YAG single crystal was employed with considerations to the dynamics and the symmetry requirements. The Stark effect of the Ce 3+ ion was observed and measured. When demonstrated as a quantum phase gate, the electric field manipulation exhibited high efficiency which allowed up to 57 π/2 operations before decoherence with optimized field direction. It was also utilized to carry out quantum bang-bang control, as a method of dynamic decoupling, and the refined Deutsch-Jozsa algorithm. Our experiments highlighted rare-earth ions as potentially applicable qubits because they offer enhanced spin-electric coupling which enables high-efficiency quantum manipulation. Abstract : We utilized the strong spin-orbit coupling in a Ce:YAG single crystal to demonstrate efficient coherent manipulation with the electric field on this electron spin qubit.